2020
DOI: 10.1186/s40658-020-0280-9
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous 166Ho/99mTc dual-isotope SPECT with Monte Carlo-based downscatter correction for automatic liver dosimetry in radioembolization

Abstract: Background: Intrahepatic dosimetry is paramount to optimize radioembolization treatment accuracy using radioactive holmium-166 microspheres (166 Ho). This requires a practical protocol that combines quantitative imaging of microsphere distribution with automated and robust delineation of the volumes of interest. To this end, we propose a dual isotope single photon emission computed tomography (SPECT) protocol based on 166 Ho therapeutic microspheres and technetium-99 m (99m Tc) stannous phytate, which accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…To minimize patient motion, 99m Tcstannous phytate was administered while the patient remained on the SPECT/CT table in supine position. The optimal 166 Ho-99m Tc ratio, yielding a high accuracy in DI reconstruction, was previously empirically determined by van Rooij et al [9] in our institution, based on phantom data, and the resulting 5:1 166 Ho-99m Tc activity ratio was adopted for this study.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…To minimize patient motion, 99m Tcstannous phytate was administered while the patient remained on the SPECT/CT table in supine position. The optimal 166 Ho-99m Tc ratio, yielding a high accuracy in DI reconstruction, was previously empirically determined by van Rooij et al [9] in our institution, based on phantom data, and the resulting 5:1 166 Ho-99m Tc activity ratio was adopted for this study.…”
Section: Study Populationmentioning
confidence: 99%
“…In previous work, van Rooij et al [9] demonstrated the technical feasibility of quantitative 166 Ho SPECT reconstructions in the presence of 99m Tc in a phantom study. These reconstructions were obtained using the in-house developed Monte Carlo SPEC T reconstruction software (UMCS).…”
Section: Introductionmentioning
confidence: 99%
“…To minimize patient motion, 99m Tc-stannous phytate was administered while the patient remained on the SPECT/CT table in supine position. The optimal 166 Ho -99m Tc ratio, yielding a high accuracy in DI reconstruction, was previously empirically determined by van Rooij et al [9] in our institution, based on phantom data, and the resulting 5:1 166 Ho -99m Tc activity ratio was adopted for this study.…”
Section: Image Acquisitionmentioning
confidence: 99%
“…In previous work, van Rooij et al [9] demonstrated the technical feasibility of quantitative 166 Ho SPECT reconstructions in the presence of 99m Tc in a phantom study. These reconstructions were obtained using in-house developed Monte Carlo SPECT reconstruction software (UMCS).…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, MRI-guided catheter-based vascular interventions are scarce and, to the best of our knowledge, no clinically available angiography catheters and guidewires are registered as MR-conditional for use at 3 Tesla (T) [18]. Additionally, previous studies into imaging 166 Ho microspheres with MRI [14][15][16] and SPECT [19,20] have mainly focused on the quantification once the microspheres are already lodged in the liver arterioles, i.e., in their final position. Ideally, MRI guidance would also be used to visualise the loss of signal caused by the microspheres in near real-time during administration, in order to be able to terminate the administration of microspheres if stasis or backflow occur.…”
Section: Introductionmentioning
confidence: 99%